Mobile service marketplace: a new channel to connect physical service providers and consumer? - Kee, Muh Shyan; Wong, Cindy Khai Xin; Kiat, Yu Hang; Ting, Siew Hui; Yeow, Jie Ming (2019)
Explosive digital growth has transformed the global society into a mobile-oriented society. The mobile commerce market has become a favourable blooming market. Mobile service marketplace (MSM), which is one of the mobile commerce applications, is growing rapidly all over the globe. In Malaysia, although MSM is at introductory stage, it is expected to develop exponentially in the near future. Nevertheless, Malaysian researchers did not focus on MSM despite numerous studies were done on mobile commerce. Hence, this research intends to bridge the gap by exploring the determinants affecting users’ trust and behavioural intention towards adopting MSM in Malaysia. Specifically, this study aims to examine the influence of system traits (ie. system quality, information quality and service quality) and personal traits (ie. social influence, facilitating conditions and self-efficacy) on user trust towards MSM. This study adopts Stimulus-Organism-Response (S-O-R) framework in studying the user behavioural intention to use MSM when they are stimulated by various traits. A cross-sectional study was conducted and a total of 540 questionnaires were being administered at various shopping malls in Malaysia. 510 responses were collected back and 490 responses were usable. This is one of the few researches that integrates system and personal traits to investigate user trust and behavioural intention towards using MSM. For hypothesis testing, this study employed multiple linear regression and simple linear regression. The results indicated that information quality, social influence, facilitating conditions and self-efficacy have positive and significant relationship on trust towards MSM. Trust was also found to be significant towards BI of MSM adoption. MSM developers and physical service providers may adopt the findings from this study to design an effective marketing strategy which meets users’ requirement in various traits.